Marketing research : an aid to decision making - Shao, Alan T. (Cincinnati, Ohio : South-Western/Thomson Learning, 2002)
How does marketing research affect your daily life? With Marketing Research: An Aid to Decision Making, 2e, students find out how marketing research processes and results lead to the marketing decisions that impact their daily lives. This book also teaches students about the important issues and methods involved in conducting marketing research, and then using the findings to manipulate the marketing mix to meet customer needs. Reviews of statistics and key marketing concepts help students brush up on the basics as they learn more about the marketing research tools and uses. A strong Internet focus keeps students in touch with the latest marketing research technologies. Students also learn how to effectively use the Internet to gather market research data more quickly and efficiently.
Includes bibliographical references and index.
Keywords: Marketing research